Neue Oniticellinen-Arten. 119. Beitrag zur Kenntnis der Scarabaeoidea (Coleoptera). - Balthasar, Vladimir (Contributions to Entomology = Beiträge zur Entomologie, 1964)
There are described 3 new species of the tribe Oniticellini (Fam. Scarabaeidae) from the tropic Africa and from Madagaskar. The description of Oniticellus (s. str.) pseudoplanatus n. sp. shows that a frequent species, which is represented in all important collections, was for a long time misinterpreted and wrongly named mixed with much related species. The strange thing is that excellent workers in Scarabaeid beetles have revised the whole tribe more than once without having noticed the misinterpretation. Nomenclatural Actshalffteri Balthasar, 1964 (Helictopleurus), spec. n.ferreirae Balthasar, 1964 (Liatongus), spec. n.pseudoplanatus Balthasar, 1964 (Oniticellus (Oniticellus)), spec. n.